Shareholders’ agreement as a type of civil contract - Serobyan, Davit; Soghomonyan, Ashkhen (Bulletin of Yerevan University C: Jurisprudence, 2021)
The objective needs for the development of legal means of regulating relations between shareholders have caused the emergence of a structure of shareholders’ agreements widespread in international practice, which, despite the high interest in it from the scientific community, has not acquired unambiguous and universal forms of legislative regulation, doctrinal and judicial-practical interpretation. This article is devoted to a shareholders’ agreement, which is characterized as one of the ways to effectively exercise the right of participants to manage a joint-stock company. Within its framework, the analysis of the concept of the indicated civil law structure is made. In the absence of the practice of applying the new legislation on shareholders’ agreements, such an analysis is of considerable interest.